Confidential U.S. State Department central files. internal affairs, decimal numbers 786A, 886A, and 986A, and foreign affairs, decimal numbers 686A and 611.86A (1950)
Correspondence of the U.S. State Department concerning internal and foreign affairs of Saudi Arabia, including despatches, telegrams, maps and charts.